Undifferenced and Uncombined GNSS Time Transfer and its Space Applications - Mi, Xiaolong (Curtin University, 2023)
This thesis presents a framework for developing a state-of-the-art undifferenced and uncombined (UDUC) time transfer technique for space applications. It addresses challenges in GNSS time transfer, such as multi-frequency signal modelling, satellite clock estimation, and hardware delay variations. The thesis introduces the UDUC POD method for GNSS time transfer in space and explores the feasibility of constructing a LEO-based space-time reference. This PhD dissertation is among the first to investigate the UDUC GNSS time transfer.